Analysis of 2013 Curriculum Implementation in Elementary Schools - Bebasari, Mardiani; Nelwatri, Helpi; Sandra, Rhona; Gistituati, Nurhizrah; Bentri, Alwen (Bisma The Journal of Counseling, 2022)
This study aims to obtain an overview of implementation, analyze and formulate problem-solving strategies in implementing the 2013 curriculum at SD Negeri Padang City. This study uses a qualitative method, with a phenomenological approach. The results of the study show that the implementation of the 2013 curriculum mostly refers to Permendikbud No. 81A 2013 regarding the implementation of the 2013 curriculum. Then the results of the analysis show that the curriculum does not contain the unique content of the education unit which is the hallmark of the curriculum at SD Negeri Gunung Pangilun, Padang City. The 2013 curriculum is still limited, learning support facilities such as LCD, laptop, wireless, additional library books and air conditioning are still limited, infrastructure facilities such as science laboratory buildings, language fields and sports are not yet available. In addition, the problem-solving strategy used requires the design of an in-house training program to increase the understanding of teachers and parents regarding the implementation of the 2013 curriculum. LCD, laptop, wireless, additional library books and air conditioning, require infrastructure support in the form of procurement of science laboratory buildings, language laboratories and sports fields.